Applications of Graphene and Graphene Oxide in Smart Drug/Gene Delivery: Is the World Still Flat? - Hoseini-Ghahfarokhi M (Dove Medical Press, 2020)
Mojtaba Hoseini-Ghahfarokhi,1,2 Soroush Mirkiani,3 Naeimeh Mozaffari,4 Mohamad Amin Abdolahi Sadatlu,5 Amir Ghasemi,6,7 Somayeh Abbaspour,6 Mohsen Akbarian,8 Fatemeh Farjadain,8 Mahdi Karimi9 1Nano Drug Delivery Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran; 2Radiology and Nuclear Medicine Department, School of Paramedical Sciences, Kermanshah University of Medical Sciences, Kermanshah, Iran; 3Neuroscience and Mental Health Institute, Faculty of Medicine and Dentistry, University of Alberta, Edmonton, Canada; 4Research School of Electrical, Energy and Materials Engineering, The Australian National University, Canberra 2601, Australia; 5Department of Engineering and Science, Sharif University of Technology-International Campus, Kish, Iran; 6Department of Engineering, Durham University, Durham DH1 3LE, United Kingdom; 7Advanced Nanobiotechnology and Nanomedicine Research Group (ANNRG), Iran University of Medical Sciences, Tehran, Iran; 8Pharmaceutical Sciences Research Center, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 9Iran Cellular and Molecular Research Center, Iran University of Medical Sciences, Tehran, IranCorrespondence: Fatemeh FarjadainPharmaceutical Sciences Research Center, School of Pharmacy, Shiraz University of Medical Sciences, P.o. Box 71345-1583, Shiraz, IranTel +987132424127 (302)Fax +987132424126Email farjadian_f@sums.ac.irMahdi KarimiDepartment of Medical Nanotechnology, Faculty of Advanced Technologies in Medicine, Iran University of Medical Sciences, Tehran, IranEmail m_karimy2006@yahoo.comAbstract: Graphene, a wonder material, has made far-reaching developments in many different fields such as materials science, electronics, condensed physics, quantum physics, energy systems, etc. Since its discovery in 2004, extensive studies have been done for understanding its physical and chemical properties. Owing to its unique characteristics, it has rapidly became a potential candidate for nano-bio researchers to explore its usage in biomedical applications. In the last decade, remarkable efforts have been devoted to investigating the biomedical utilization of graphene and graphene-based materials, especially in smart drug and gene delivery as well as cancer therapy. Inspired by a great number of successful graphene-based materials integrations into the biomedical area, here we summarize the most recent developments made about graphene applications in biomedicine. In this paper, we review the up-to-date advances of graphene-based materials in drug delivery applications, specifically targeted drug/ gene delivery, delivery of antitumor drugs, controlled and stimuli-responsive drug release, photodynamic therapy applications and optical imaging and theranostics, as well as investigating the future trends and succeeding challenges in this topic to provide an outlook for future researches.Keywords: graphene, graphene oxide, drug delivery, gene delivery, cancer therapy, photodynamic therapy